1999
DOI: 10.1148/radiology.210.1.r99ja46269
|View full text |Cite
|
Sign up to set email alerts
|

Regional Blood Flow, Capillary Permeability, and Compartmental Volumes: Measurement with Dynamic CT—Initial Experience

Abstract: Sequential computed tomographic scanning was performed in patients with neck tumors after contrast material administration. For data analysis, a pharmacokinetic two-compartment model was employed that takes into account both capillary blood supply and bidirectional diffusion of the contrast agent across the capillary wall. This approach offers the possibility to quantitatively characterize tissue microcirculation with regional blood flow, capillary permeability, and relative compartmental volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
138
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(147 citation statements)
references
References 39 publications
6
138
1
2
Order By: Relevance
“…While R CC1 (t) may be applicable for cerebral perfusion imaging, R CC2 (t) has been used in DCE MRI studies of various tumors (38)(39)(40)(41)(42)(43)(44)(45). Mammillary three-compartment CC models have also been devised for DCE MRI of the brain (46)(47)(48) and breast tumors (49), which revealed that tumor tissues can demonstrate kinetic heterogeneity with two or more interstitial compartments having different exchange rates.…”
Section: Conventional Compartmental (Cc) Modelsmentioning
confidence: 99%
“…While R CC1 (t) may be applicable for cerebral perfusion imaging, R CC2 (t) has been used in DCE MRI studies of various tumors (38)(39)(40)(41)(42)(43)(44)(45). Mammillary three-compartment CC models have also been devised for DCE MRI of the brain (46)(47)(48) and breast tumors (49), which revealed that tumor tissues can demonstrate kinetic heterogeneity with two or more interstitial compartments having different exchange rates.…”
Section: Conventional Compartmental (Cc) Modelsmentioning
confidence: 99%
“…The delays a and p were defined to be equal and were fixed to the delay between the first nonzero value of the C a (t) curve and the first nonzero value of the C L (t) curve. The small vessel hematocrit (Hct SV ) was set to a constant value of 0.25 (31). The concentration vs. time curves were then fitted to the compartmental model.…”
Section: Microsphere Measurementsmentioning
confidence: 99%
“…Blood dilution was implemented in order to simulate conditions of physiological variability of hematocrit across systemic vasculature and capillary networks. 30 PBS (pH 7.4) was used to dilute the whole blood while preserving the integrity of red blood cells. Optoacoustic imaging was performed while slowly decreasing the temperature from þ37 to À15 C. As an acoustically coupling medium, we used aqueous solution of sodium chloride at its eutectic concentration (23 wt.…”
mentioning
confidence: 99%